Torah and Divine Revelation in Three Jewish Texts: 4QInstruction, Wisdom of Solomon and the Fourth Gospel. (June 2022) - Hubbard, Jeffrey
Studies of the sapiential traditions in the Fourth Gospel remain unfortunately insulated from recent research into the fluid relationship between wisdom and apocalypticism in early Judaism. The well-known connection made between wisdom and Torah in Sirach and Baruch leads many scholars to mischaracterize John's perspective on Law as incongruous with Jewish sapientialism. However, appropriate consideration of the interconnection between wisdom and apocalypticism demonstrates the error of this characterization. This article compares the relationship between wisdom and Torah in 4QInstruction, the Wisdom of Solomon, and the Gospel of John. Both Wisdom and 4QInstruction offer instructive comparanda for the Fourth Gospel's presentation of wisdom. The article proceeds in essentially two parts. First, I consider the role of the law in 4QInstruction and the Wisdom of Solomon, arguing that each of these very different texts subordinates the written law to a revealed heavenly wisdom. Then, in critical dialogue with the work of the late John Ashton, I reexamine the relationship between divine revelation and Torah in John and suggest that the Fourth Gospel is most fruitfully read as another example of the fluid boundaries between wisdom and apocalypticism in early Judaism.